Peculiarities of the composition of surface and groundwater in eastern Ukraine during the war: assessment of environmental and carcinogenic risks - Kovalov, O. O.; Kolesnyk, Yu. М.; Sevalniev, А. І.; Hancheva, О. V.; Sharavara, L. P.; Kovalov, К. О.; Tyshchenko, Т. М.; Tulushev, Ye. О.; Ковальов, Олексій Олексійович; Колесник, Юрій Михайлович; Севальнєв, Анатолій Іванович; Ганчева, Ольга Вікторівна; et al. (Запорізький державний медико-фармацевтичний університет, 2025)
Aim. To study the content of environmental toxins, organic compounds and heavy metals in surface and ground waters in the south-east of Ukraine near the frontline and to identify areas of high risk of pollution. Materials and methods. During the period of 2024, 70 drinking water samples were collected and examined from the centralised water supply networks of the city of Zaporizhzhia of the Municipal Enterprise “Vodokanal” and Enterprise of State Criminal-Executive Service of Ukraine. Groundwater samples were taken by professional hydrogeologists on November 9, 2024, near Tarasivka village (geographical coordinates: 47°46′41′′N 35°26′36′′E / 47.77806°N 35.44333°E) and near Vilne village (geographical coordinates: 47.57286°N 32.61995°E) of Komyshuvakha village, Orikhiv district, Zaporizhzhia region, at a depth of 5, 14 and 190 meters. The water was not preserved and was delivered to the laboratory within a few hours. The chemical analysis was carried out in the laboratory of Ukrkhimanaliz LLC of the Center for Preventive Medicine of the State Administration of Affairs. The presence of heavy metals and organic compounds (50 indicators in total) was studied by atomic emission spectral, photometric, titrimetric, ionometric, colorimetric, chromatographic and calculation methods. Мета роботи – дослідити вміст екологічних токсинів, органічних сполук і важких металів у поверхневих і ґрунтових водах південного сходу України біля лінії фронту, визначити зони високого ризику забруднення. Матеріали і методи. Протягом 2024 року з водопровідних мереж централізованого водопостачання м. Запоріжжя КП «Водоканал» і ДП «Підприємство державної кримінально-виконавчої служби України» відібрано та досліджено 70 проб питної води. Відбір 30 проб підземних вод здійснено професійними працівниками-гідрогеологами 09 листопада 2024 року біля села Тарасівка (географічні координати: 47°46′41″ пн. ш. 35°26′36″ сх. д. / 47.77806°пн. ш. 35.44333°сх. д.) та біля села Вільне (географічні координати: 47.57286 пн. ш., 32.61995 сх. д.), селища Кoмишуваха Оріхівського району Запорізької області на глибині залягання 5 м, 14 м і 190 м (по 10 проб на кожній локації). Воду не консервували і доставляли до лабораторії протягом кількох годин. Хімічний аналіз здійснено в лабораторії ТОВ «Укрхіманаліз» Центру превентивної медицини Державного управління справами. Наявність важких металів і органічних сполук (всього 50 показників) вивчали атомно-емісійним спектральним, фотометричним, титриметричним, іонометричним, колориметричним, хроматографічним і розрахунковим методами.
Особливості складу поверхневих і ґрунтових вод сходу України під час війни: оцінювання екологічних і канцерогенних ризиків
Keywords: assessment of environmental and carcinogenic risks; composition of surface and ground waters; water quality; Ukraine; military operations; оцінювання екологічних і канцерогенних ризиків; склад поверхневих і підземних вод; якість води; Україна; бойові дії